Prawa człowieka a „śmierć Boga” - Sulikowski, Adam (Wydawnictwo Uniwersytetu Wrocławskiego, 2017)
The “death of God” — a Nietzschean metaphor — is still considered as an excellent diagnosis of the condition of modern societies deprived of metaphysical ground. The author uses this metaphor to illustrate the genealogy and the present of conservative criticism of human rights. This criticism is based on the allegation that the ideology of human rights is responsible for the breakdown of the “social metaphysics” of the West. The author attempts to show the dangerous potential of conservative criticism of human rights. In the following part of his paper the author refers to the phenomenon of “the end of grand narratives” treated as another dimension of the “death of God” and formulates the question of possible solutions to the problem of justification of human rights in postmodern conditions.
Keywords: prawa człowieka; "śmierć Boga"